2018
DOI: 10.31230/osf.io/c5xqb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why people matter in ocean governance: Incorporating human dimensions into large-scale marine protected areas

Abstract: Large-scale marine protected areas (LSMPAs) are rapidly increasing. Due to their sheer size, complex sociopolitical realities, and distinct local cultural perspectives and economic needs, implementing and managing LSMPAs successfully creates a number of human dimensions challenges. It is timely and important to explore the human dimensions of LSMPAs. This paper draws on the results of a global "Think Tank on the Human Dimensions of Large Scale Marine Protected Areas" involving 125 people from 17 countries, inc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 61 publications
0
49
0
Order By: Relevance
“…This is exemplified by the increasing number of individuals and organizations -including local communities, practitioners, academics and NGOs -that are calling for a foundational set of guiding principles or social standards to guide conservation practitioners [28,[54][55][56]. Notably, one outcome of a recent global Think Tank on the Human Dimensions of Large Scale Marine Protected Areas -attended by more than 125 scholars, practitioners, funders and managers from around the world -was a call by a group of those present for the development of such a code of conduct for marine conservation [57,58]. Many other professions, including doctors, lawyers, engineers, accountants and teachers, have codes of conduct to establish a firm foundation for practice.…”
Section: Marine Conservation: In Need Of a Social Standardmentioning
confidence: 99%
“…This is exemplified by the increasing number of individuals and organizations -including local communities, practitioners, academics and NGOs -that are calling for a foundational set of guiding principles or social standards to guide conservation practitioners [28,[54][55][56]. Notably, one outcome of a recent global Think Tank on the Human Dimensions of Large Scale Marine Protected Areas -attended by more than 125 scholars, practitioners, funders and managers from around the world -was a call by a group of those present for the development of such a code of conduct for marine conservation [57,58]. Many other professions, including doctors, lawyers, engineers, accountants and teachers, have codes of conduct to establish a firm foundation for practice.…”
Section: Marine Conservation: In Need Of a Social Standardmentioning
confidence: 99%
“…Previous studies of prairie lakes have identified key chemical, biological, climatic, and anthropogenic controls of food‐web diversity; however, the human dimensions of these complex socio‐ecological systems (SES) are not as well understood. The absence of recognition of human dimensions can lead to an incomplete understanding of the coupling between biophysical and human systems and a failure to meet management objectives (Bennett ; Echeverri et al ), which are dependent on public support and modification of human behaviors (Christie et al ). Despite recent efforts to incorporate the social dimensions of human systems into ecosystem management, governance of natural resources still overlooks the importance of stakeholder values and perceptions (Bennett ), thereby obscuring the role of human behavior in the SES being studied (Adams and Sandbrook ).…”
Section: Human Dimensions Of Complex Socio‐ecological Systemsmentioning
confidence: 99%
“…Despite recent efforts to incorporate the social dimensions of human systems into ecosystem management, governance of natural resources still overlooks the importance of stakeholder values and perceptions (Bennett ), thereby obscuring the role of human behavior in the SES being studied (Adams and Sandbrook ). Stakeholder perceptions may not be accurate or factual, but it is important to understand their values, knowledge, and opinions regarding an SES because stakeholder perceptions inform opinions on management objectives and identify how likely the public is to comply with regulatory measures (Brown et al ; Bennett ; Christie et al ). Successfully integrating human and ecological dimensions of SES often require either an interdisciplinary or transdisciplinary research approach to both advance scientific knowledge and develop effective management solutions (Cook et al ).…”
Section: Human Dimensions Of Complex Socio‐ecological Systemsmentioning
confidence: 99%
“…Protected areas are considered an effective method of managing human activities and natural resources (Christie et al, ; Laffoley et al, ; Organisation for Economic Co‐operation and Development, ). The CBD defines protected areas as ‘a geographically defined area, which is designated or regulated and managed to achieve specific conservation objectives’.…”
Section: Introductionmentioning
confidence: 99%